THE ROLE OF BACTERIAL BIOFILM IN REFRACTORY CHRONIC RHINOSINUSITIS: A NARRATIVE REVIEW - Oliwia Sójkowska-Sławińska; Tobiasz Sławiński; Anna Leśniewska; Patryk Macuk; Michał Gniedziejko; Jakub Roszak; Paulina Bernecka; Bartosz Michał Skorupski; Natalia Strumnik (International Journal of Innovative Technologies in Social Science, 2025)
Objectives: Chronic Rhinosinusitis (CRS) is a common inflammatory disease impacting 5-12% of the population, leading to substantial morbidity and healthcare expenses. Bacterial biofilms on the sinonasal mucosa are a key factor in CRS’s development, persistence, and resistance to treatment. This review explores their role in refractory CRS, focusing on structure, formation, impact on severity, and diagnostic/therapeutic approaches. Methods: We conducted a comprehensive literature review using PubMed, Scopus, and Web of Science, searching for keywords related to CRS, bacterial biofilms, antibiotic resistance, and therapies. We prioritized studies from the last decade examining biofilms’ impact on CRS pathogenesis, resistance, and novel treatments. Key findings: Biofilms, organized microbial communities within an extracellular polymeric matrix, are significantly more resistant to antibiotics and host immune responses than free-floating bacteria. They form through stages: initial attachment, proliferation, and complex 3D structure development, with quorum sensing vital for maturation. Common CRS biofilm pathogens include Staphylococcus aureus, Pseudomonas aeruginosa, and Haemophilus influenzae. Biofilms correlate with more severe disease, poorer surgical outcomes, and higher recurrence. Diagnostics include electron microscopy, confocal laser scanning microscopy (CLSM), and molecular methods. Treatment involves surgical removal, topical antibiotics, and novel strategies like phage therapy, quorum sensing inhibitors, and micro-biome-based interventions. Conclusions: Biofilms are critical in refractory CRS, causing persistence, treatment resistance, and worse outcomes. A deep understanding of biofilm mechanisms is crucial for effective diagnostics and therapies. Future research should standardize diagnostics, clarify biofilm-host interactions, and conduct trials on new, personalized biofilm-targeting treatments.